HUBUNGAN KADAR CRP DAN D-DIMER DENGAN DERAJAT KEPARAHAN PASIEN COVID-19 DI RSPAD GATOT SOEBROTO PERIODE 2020-2022 - Nicolas Bondan Pradipto (2024)
COVID-19 has clinical manifestations ranging from asymptomatic mild symptoms to severe symptoms that can lead to acute respiratory distress syndrome (ARDS), multiple organ failure and death. Biomarkers such as C-reactive protein (CRP) and D-dimer play a role in the diagnosis, assessment of severity, prognosis and mortality of patients. CRP and D-dimer are biomarkers whose serum concentrations tend to increase in COVID-19 patients. Method: This is a cross-sectional study to determine the relationship between serum CRP and D-dimer concentrations and the severity of COVID-19 inpatients. This study uses secondary data from medical records of patients over 18 years of age with a diagnosis of COVID-19 who meet the inclusion and exclusion criteria. Result: The results of statistical tests show that there is a significant relationship between CRP and D-dimer concentrations and the severity of COVID-19 inpatients (p value = 0.000). Conclusion: There is a significant relationship between serum CRP and D-dimer concentrations on the degree of severity.